Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0062857
|View full text |Cite
|
Sign up to set email alerts
|

The SOX2-Interactome in Brain Cancer Cells Identifies the Requirement of MSI2 and USP9X for the Growth of Brain Tumor Cells

Abstract: Medulloblastomas and glioblastomas, the most common primary brain tumors in children and adults, respectively, are extremely difficult to treat. Efforts to identify novel proteins essential for the growth of these tumors may help to further our understanding of the biology of these tumors, as well as, identify targets for future therapies. The recent identification of multiple transcription factor-centric protein interaction landscapes in embryonic stem cells has identified numerous understudied proteins that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 56 publications
7
74
0
Order By: Relevance
“…This D1 peptide has strong homology to both Sox2 ( Figure 2) and TIF1A (Supplementary Figure 3A), which are transcriptional co-regulators [46,47]. Intriguingly, a recent study documented an interaction between Sox2 with TAF2 via immunopurification of Sox2 followed by MudPIT analysis [31], which is consistent with our D1-peptide label transfer results ( Figure 4A). We have also confirmed a direct interaction between Sox2 and TFIID using peer-reviewed) is the author/funder.…”
Section: Correlation Between Tfiid Subunits Targeted By Selected Peptsupporting
confidence: 90%
See 1 more Smart Citation
“…This D1 peptide has strong homology to both Sox2 ( Figure 2) and TIF1A (Supplementary Figure 3A), which are transcriptional co-regulators [46,47]. Intriguingly, a recent study documented an interaction between Sox2 with TAF2 via immunopurification of Sox2 followed by MudPIT analysis [31], which is consistent with our D1-peptide label transfer results ( Figure 4A). We have also confirmed a direct interaction between Sox2 and TFIID using peer-reviewed) is the author/funder.…”
Section: Correlation Between Tfiid Subunits Targeted By Selected Peptsupporting
confidence: 90%
“…TAF2, 3, or 4) cross-linked to the SBED-labeled GST-peptides. However, a recent study using immunopurification of Sox2 followed by MudPIT analysis revealed an interaction between Sox2 with TAF2 [31]. It is thereby likely that the GST-D1 peptide contacts TAF2 in this experiment.…”
Section: Characterization Of Select Tfiid-binding Peptidesmentioning
confidence: 62%
“…In addition, Msi2 isoform 2 appears to be the major isoform expressed in bladder cancer cell lines and tissues, which was consistent with the expression pattern of Msi2 in glioblastoma cells and embryonic stem cells. 18,19 Clinical analysis also indicated that high expression of Msi2 was correlated with poor overall and Msi2 promotes bladder cancer metastasis via JAK2/STAT3 pathway C Yang et al recurrence-free survival in patients with bladder cancer. Moreover, in vitro assays indicated that overexpression of Msi2 promoted, while silencing of Msi2 inhibited, the migration and invasiveness of bladder cancer cell through activating JAK2/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Msi2 expression was negatively Msi2 promotes bladder cancer metastasis via JAK2/STAT3 pathway C Yang et al associated with AML patients outcome, 21 while the expression of NUMB, which was negatively regulated by Msi2 both in vitro and in vivo, 19 was not associated with overall survival in AML patients. 22 Mu et al 23 reported that high Msi2 expression could indicate poor prognosis in adult B-cell acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, CSCs were identified in a murine brain tumor population by expressing EGFP under the control of nucleostemin promoter (a p53 mediate cell cycle modulator often expressed by highly proliferative cells) (Tamase, Muraguchi et al 2009). Furthermore, screening of BTSCs using flow-cytometry and Elisa have identified CD133, MMP-9, nestin, Pax6, Math-1, musashi-1, BMI-1, CXCR4, CX3CR1, c-Myc and Sox2 expressing BTSCs from both gliomas and medulloblastomas (Tamase, Muraguchi et al 2009, Cox, Wilder et al 2013, Sullivan, Nahed et al 2014). 1) High expression acts as an independent prognosis marker for malignant gliomas (Krogh Petersen, Jensen et al 2016).…”
Section: Diagnostic Approach To Identify Btscsmentioning
confidence: 99%